Entrepreneur Cybernetics - Soylu, Ali (European Scientific Journal, ESJ, 2016)
Cybernetics, which was accepted as a method of designing automatic machines by El-Cezeri who was a physicist lived in the 12th century, is a branch of science that examines the supervision and management of animate and inanimate complex systems. Cybernetics, which was considered as a scientific concept in 1948 by American mathematician and philosopher Norbert Wiener, includes an interdisciplinary approach based on the research of regular systems and the structure, limit and capability of these systems. The mechanical, physical, biological, social and intellectual systems can be subjects of cybernetics. In this context, in the length of time, the concept of cybernetics has been enlarged by covering social sciences, economics and management sciences by Canadian scientist Stafford Beer and others, and its interests diversified (Ergen, 2014, p. 18). Cybernetics has the possibility of being used on the subject of entrepreneurship which has increased its importance nowadays. Especially in the identification of the entrepreneurial mechanism of countries, cybernetics can be taken as a reference point that can be applied to understand the formation and functioning of the entrepreneurial ecosystem. Entrepreneurial cybernetics has an approach that involves entrepreneurial quality, capital risk tendency and state mechanisms of a country. The aim of this study is to develop an approach based on building a structure in which all parties related to entrepreneurship can collaborate and entrepreneurship ecosystem can be balanced in its own. The study of entrepreneurial cybernetics includes a theoretical approach on this subject.